Accessibility and inclusion in higher education: an inquiry of faculty perceptions and experiences - McGinty, Jacqueline M., author; Gloeckner, Gene, advisor; Kaiser, Leann, advisor; Folkestad, James, committee member; Scott, Malcolm, committee member (Colorado State University. Libraries, 2016)
Although there are an increasing number of students with disabilities attending institutions of higher education, the graduation rate for students with disabilities lags behind that of non-disabled college students attending similar institutions. College faculty members produce academic content, determine learning outcomes, and determine assessment protocol. As primary gatekeepers of academic achievement, college faculty members are instrumental in the provision of academic accommodations for students with disabilities. Faculty members in the College of Engineering and in the College of Health and Human Sciences at Colorado State University were invited to participate in answering a survey on accessibility and academic accommodations for students with disabilities. The purpose of this study was to identify faculty issues and concerns regarding accommodations for students with disabilities and to make suggestions that lead to increased faculty utilization of accessible learning materials. This research intends to improve the learning environment for students with disabilities by recommending and disseminating inclusive teaching practices to improve accessibility of higher education so that all students can acquire the same information and participate in the same activities in a similar manner as students without disabilities.